2022
DOI: 10.1039/d1ta08646d
|View full text |Cite
|
Sign up to set email alerts
|

Structural design and mechanism analysis of hierarchical porous carbon fibers for advanced energy and environmental applications

Abstract: The progress in the synthesis of porous carbon fibers and their performance improvement mechanisms for energy and environmental applications are comprehensively reviewed, providing guidelines for the future development of this emerging material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 412 publications
(530 reference statements)
1
17
0
Order By: Relevance
“…The MOF structure has played a vital role in recent research, and it is necessary to elaborate on the molecular properties of MOFs such as surface area, functionality, molecular arrangement, and morphology. These understandings are valuable from an application perspective. , The imidazole molecule has two functional (nitrogen) sites, whereas adenine has five reactive sites. The possible structural formation of the molecule is as follows: The Imz-MOF has two free functional groups that can network with nickel ions and form a chain effortlessly, and the square- and cubic-type frameworks are commonly represented as two-dimensional (2D)-type MOFs .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MOF structure has played a vital role in recent research, and it is necessary to elaborate on the molecular properties of MOFs such as surface area, functionality, molecular arrangement, and morphology. These understandings are valuable from an application perspective. , The imidazole molecule has two functional (nitrogen) sites, whereas adenine has five reactive sites. The possible structural formation of the molecule is as follows: The Imz-MOF has two free functional groups that can network with nickel ions and form a chain effortlessly, and the square- and cubic-type frameworks are commonly represented as two-dimensional (2D)-type MOFs .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The SC can deliver a short-range and high power density but has a low energy density. This disadvantage was overcome by increasing the cell voltage capacitance, which was achieved by increasing the interface interaction between the electrolytes and the active materials. Numerous materials have been proposed for developing SCs, such as metal–organic framework (MOF) materials, metal oxides, carbon-based materials, and organic and polymer molecules. The development of a novel material involves focusing on enhancing the efficiency of the device, concerning the molecular architecture, high surface area, porous structure, and active ions. MOFs are rich enough to demonstrate high efficiency in SC applications.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the peaks at 786.4 and 802.8 eV confirm the satellite peaks of Co 2+ . 56,57 It was observed that the electronic structure of cobalt in the CuCo 2 O 4 /H-gC 3 N 4 /3D-rGO composite was shifted slightly to a higher binding energy due to the effect of N species. The binding energy at 933.4 eV in the highresolution Cu 2p 3/2 spectrum indicated the presence of Cu 2+ in the octahedral position in the composite.…”
Section: Structure and Morphology Of The Cuco 2 Omentioning
confidence: 99%
“…The derivatives possess a light weight, a high dielectric constant, and magnetic uniformity, which exhibits outstanding advantages in the electromagnetic field . In addition, derivatives exhibit the structural advantages of a large surface area and uniform pore distribution, which can generate abundant interface genes, expand the conductive network, cause strong multiple scattering and reflection of electromagnetic waves, and further achieve excellent EMI shielding effectiveness (EMI SE). Carbon cloth shows excellent electrical conductivity, and loading a small amount of conductive material on the surface can form a double conductive layer structure. , Compared with the expensive commercial carbon cloth, carbon cloth derived from cotton fabric (CF) possesses a wide range of raw materials and further can save costs. However, MOF@fabric and their derivatives for electromagnetic shielding have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…24−27 Carbon cloth shows excellent electrical conductivity, and loading a small amount of conductive material on the surface can form a double conductive layer structure. 28,29 Compared with the expensive commercial carbon cloth, carbon cloth derived from cotton fabric (CF) possesses a wide range of raw materials and further can save costs. However, MOF@fabric and their derivatives for electromagnetic shielding have not been reported.…”
Section: Introductionmentioning
confidence: 99%